A New Route to Fabricate Multifunctional and Multistage Composite Nanoparticle - Xin Wang; Pin Chen; Xiaohong Hu (International Journal of Polymer Science)
The focus of nanoparticle research is on exploring its application in all kinds of field. Among these, multifunctional nanoparticle attracts increasing interest due to its fittest property and adjustable property. Herein, a multifunctional and multistage nanoparticle considering the advantage of both nanogel and pH-responsive property has been designed and synthesized in the research. The composite nanoparticle was obtained by in situ processing and polymerization technique using acetylated β-cyclodextrin and gelatin as materials. Gelatin was first encapsulated into Ac-β-CD nanoparticle in order to investigate optimal fabrication conditions of W/O/W technique. The results showed that the nanoparticle had monodisperse characteristic and coarse spherical morphology, which was influenced by factors such as PVA concentration and water/oil ratio. In further step, two-phase composite nanoparticle could be obtained by combined W/O/W technique and in situ polymerization using optimal preparative parameters of W/O/W technique. Two-phase structure could be confirmed by TEM images and DLS results. Fabrication temperature had no effect on the diameters of composite nanoparticle, but influenced the encapsulated efficiency of nanogel. Finally, composite nanoparticle showed quick pH response property at mild acid medium and no obvious cytotoxicity.